Rancang Bangun Low Cost Wind Turbine Untuk Pengisian Baterai - Hegi Putra Pratama; Diana Alia; Maulidiah Rahmawati (Pusat Riset dan Inovasi Nasional, 2024)
Renewable energy is increasingly popular and in demand throughout the world as an alternative to increasingly limited fossil energy, one of which is wind turbines. Wind turbine research on ships has great potential in developing renewable energy at sea. The aim of this research is to increase the efficiency of converting wind energy into electrical energy by designing a low cost wind turbine and analyzing the design efficiency of the wind turbine blade angle, namely 90˚, 95˚, 100˚. This research uses an experimental method with observation techniques, as well as measurement and recording as data collection techniques. This research was conducted on the Bung Tomo training ship for 3 days. The research results show that making a wind turbine using PVC as a base material costs Rp. 243,000.00 and produces the largest average voltage of 73.8 Wh. The influence of variations in the angle of the wind turbine blade can be seen that at an angle of 100˚ it has the largest average power output, namely 1.23 watts per minute and the battery charging time is based on an average current of 0.28 A, namely 12.5 hours when fully charged, whereas at The 90˚ angle produces the smallest average power of 0.76 watts per minute and the battery charging time is 16.6 hours when fully charged. So the 100˚ angle is more effective in charging the battery than the 95˚ and 90˚ angles. The greater the blade angle, the greater the rotation and produce greater voltage, this is influenced by the area of the turbine exposed to wind.